Gold Nanoparticles Augment N-Terminal Cleavage and Splicing Reactions in Mycobacterium tuberculosis SufB - Nanda, Ananya; Nasker, Sourya Subhra; Kushwaha, Anoop K.; Ojha, Deepak Kumar; Dearden, Albert K.; Nayak, Saroj K.; Nayak, Sasmita (Frontiers in Bioengineering and Biotechnology, 2021)
Protein splicing is a self-catalyzed event where the intervening sequence intein cleaves off, joining the flanking exteins together to generate a functional protein. Attempts have been made to regulate the splicing rate through variations in temperature, pH, and metals. Although metal-regulated protein splicing has been more captivating to researchers, the metals were shown to only inhibit splicing reactions that confine their application. This is the first study to show the effect of nanoparticles (NPs) on protein splicing. We found that gold nanoparticles (AuNPs) of various sizes can increase the splicing efficiency by more than 50% and the N-terminal cleavage efficiency by more than 45% in Mycobacterium tuberculosis SufB precursor protein. This study provides an effective strategy for engineering splicing-enhanced intein platforms. UV-Vis absorption spectroscopy, isothermal titration calorimetry (ITC), and transmission electron microscopy (TEM) confirmed AuNP interaction with the native protein. Quantum Mechanics/Molecular Mechanics (QM/MM) analysis suggested a significant reduction in energy barrier at N-terminal cleavage site in presence of gold atom strengthening our experimental evidence on heightened N-terminal cleavage reaction. The encouraging observation of enhanced N-terminal cleavage and splicing reaction can have potential implementations from developing a rapid drug delivery system to designing a contemporary protein purification system.